Medical Student- and Resident-Authored Publications in Academic Medicine From 2002 to 2016: A Growing Trend and Its Implications. (March 2019) - Munzer, Brendan W.; Griffith, Max; Townsend, Whitney A.; Burk-Rafel, Jesse
Abstract : Purpose: The extent of medical trainees' engagement in scholarly medical education publication is not well described. This study sought to quantify the prevalence of medical student- and resident-authored medical education publications over 15 years, a benchmark essential for understanding current and future trends in trainee scholarship. Method: Of 91 identified journals, 16 met inclusion criteria as indexed general medical education journals. Only Academic Medicine provided complete author role information, allowing identification of medical student and resident authors. The authors retrospectively compiled and analyzed citation records from Academic Medicine from 2002 to 2016, tracking trainee authorship, author position, and publication type. Results: A total of 6, 280 publications were identified, of which 4, 635 publications, by 16, 068 authors, met inclusion criteria. Trainees were 6.0% (966/16, 068) of all authors and authored 14.5% (673/4, 635) of all publications. Trainee authorship rates varied by publication type: Trainees authored 33.3% (160/480) of medical humanities publications versus 6.9% (27/392) of commentaries. From 2002–2004 to 2014–2016, the proportion of authors who were trainees increased from 3.9% (73/1, 853) to 7.1% (330/4, 632) ( P < .001 for trend). Over the same period, the percentage of trainee-authored publications increased: 9.4% (58/620) to 18.8% (225/1, 199) ( P < .001 for trend), driven primarily by increased trainee first authorship. Conclusions: Trainees constitute a small but growing proportion of authors and authored publications in Academic Medicine . Further work is needed to understand what trainee-, institutional-, and journal-level factors contribute to this trend, and whether similar increases in trainee authorship are occurring in other journals and fields. Abstract : Supplemental Digital Content is available in the text.